2013
DOI: 10.1021/ct301063k
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Molecular Dynamics, MM–PBSA and Thermodynamic Integration Study of Saquinavir Complexes with Wild-Type HIV-1 PR and L10I, G48V, L63P, A71V, G73S, V82A and I84V Single Mutants

Abstract: A great challenge toward Acquired Immunodeficiency Syndrome (AIDS) treatment is to combat the HIV-1 virus. The major problem of drug resistance has kept the virus one step ahead of the medical community, and the call for more effective drugs remains as urgent as ever. Saquinavir, the first inhibitor against HIV-1 protease, offers the most extensive clinical data regarding resistance mutations. In this work, we examine L10I, G48V, L63P, A71V, G73S, V82A, and I84V single mutant HIV-1 PR strains in complexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
55
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 55 publications
15
55
0
1
Order By: Relevance
“…Indeed, the distance between the flap tips in the HIV PR complexes lies within ∼6–10 Å (Figure ). This suggests closed structures for the bound forms of the protease, a result that is in agreement with previous studies on similar systems . The 4 –HIV PR complex has the highest values of flap separation, which reach ∼10 Å; however, 4 is firmly anchored into the binding cavity of HIV PR during the entire simulation and it appears that a distance of 9–10 Å between flaps does not induce an open structure of the protease.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the distance between the flap tips in the HIV PR complexes lies within ∼6–10 Å (Figure ). This suggests closed structures for the bound forms of the protease, a result that is in agreement with previous studies on similar systems . The 4 –HIV PR complex has the highest values of flap separation, which reach ∼10 Å; however, 4 is firmly anchored into the binding cavity of HIV PR during the entire simulation and it appears that a distance of 9–10 Å between flaps does not induce an open structure of the protease.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies from our group have suggested that increased binding affinity for HIV PR is also observed if van der Waals interactions between the inhibitor and PR are significantly enhanced . In agreement with this observation, Ghosh et al .…”
Section: Introductionsupporting
confidence: 59%
“…Regarding the comparative performance of MM/PBSA and MM/GBSA, our results revealed that relative binding free energy estimates obtained by MM/PBSA showed a better correlation with experimental values ( r 2 = 0.73) compared to MM/GBSA ( r 2 = 0.47), thus evidencing a slightly better performance of MM/PBSA over MM/GBSA in the particular systems under study (Figure ). This result can be explained in terms of PB being more theoretically rigorous than GB despite that MM/GBSA has shown better performance in several systems, as reported in the literature . Consequently, we have concluded that both MM/PBSA and MM/GBSA are capable of reproducing the relative binding free energy trends in E‐selectin–oligosaccharide complexes with relatively low computational cost and acceptable accuracy.…”
Section: Resultssupporting
confidence: 68%
“…The protease dimer is in dynamic equilibrium between the closed conformation and various open conformational states [7]. Molecular dynamics studies suggest that mutations in the flaps or even in distal regions may affect the flap dynamics and hence the binding of PIs [89]. …”
Section: Introductionmentioning
confidence: 99%